Emulsions loaded with dihydromyricetin enhance its transport through Caco-2 monolayer and improve anti-diabetic effect in insulin resistant HepG2 cell. (January 2020) - Chen, Lei; Lin, Xiujun; Teng, Hui
Graphical abstract: Highlights: Dihydromyricetin (DMY) was encapsulated in an O/W emulsion with high efficiency. Edible emulsions possess promising potential to ameliorate insulin resistance. Emulsions loaded with DMY could promote glucose uptake and glycolysis. Abstract: Low bioavailability of dihydromyricetin (DMY) affects its in vivo bioactivity. O/W-based microemulsions of DMY (S-DMY) were established and IR-induced HepG2 cells were conducted to investigate the effect of S-DMY on glucose metabolism in the present study. It was observed that the bioaccessibility of DMY increased treblein emulsified form, as assessed by Caco-2 cell models. We also found that both S-DMY and DMY increased the glucose consumption of insulin resistant cells, and elevated the levels of insulin receptor substrate-1 (IRS-1), phosphoinositide 3-kinase (PI3K), protein kinase B (AKT), adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), as well as Acetyl-CoA Carboxylase (ACC) pathway and glucose transporter 2 (GLUT2). Reduced expressions in glucose 6 phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK) proteins were also noted, which confirmed that the emulsions loaded with DMY could also promote glucose uptake and glycolysis, inhibiting gluconeogenesis, and may via the regulation of IRS-1/PI3K/AKT pathways.